Methodology of Efficiency Assessment in the Context of Building Sustainability - Å vajlenka, Jozef; Kozlovská, Mária (International Journal of Engineering and Technology, 2018)
The construction industry has long been among the sectors with lower productivity and efficiency. In the framework of construction, the concept of sustainability is at the forefront. Basic elements of sustainability are environmental aspects, social and economic aspects associated with construction as such. The basic requirement to measure these factors is to set the criterions and draft a methodology for their evaluation. The aim of this paper is to present a methodology for assessing the effectiveness of buildings in the context of sustainability. The article also presents a preview of the evaluation of two wood-based construction technologies through the proposed efficiency assessment methodology in the context of building sustainability.Â Â